English songs to develop the speaking and listening skills in teenagers with visual impairments at “Unidad Educativa Internacional Pensionado Atahualpa” during the school year 2016-2017 - Zamora Villota, Andrea Estefany (2017)
The purpose of this study was to determine the incidence of the songs in English on the ability to hear and speak the English language in adolescents with visual disabilities at "Unidad Educativa Internacional Pensionado Atahualpa” during the school year 2016-2017, where different strategies and techniques were used for getting improvements in the listening and speaking skills of English language. I can emphasize that it was a benefit for the students, due to the songs, it gives an interactive environments for blind children, and that helps to solve the problem about listening and speaking skills. Language learning is even more important for visually impaired people, in order to reduce the gap caused by lack of sight or from severe visual impairment. I had considerated to use didactic songs repetitively and I measured the students` English level, and the development of their skills. I can emphasize that this is the age of the technology and I could find practically many songs on this website and it was a great idea to teach in this way. The attitude took by the teachers face to this process was so important and interesting, in order to sensitize the importance to be given when include people with SEN (special educational needs) in regular classrooms, and thus it makes this task fulfilled as satisfactorily as possible. Learning a second language in students with visual impairments is possible when a teacher uses the appropriate techniques and when the suitable curricular adaptations are well applied.